Utilization of the breadfruit tree (Artocarpus altilis) meal in fattening swine diets - Ort?z, Abel; Mart?, O.; Valdivi?, Manuel; Leyva, C. (Cuban Journal of Agricultural Science, 2011)
A total of 48 pigs of the Yorkland x Duroc hybrid, with initial average liveweight of 27.7 kg, was used for 70 d to evaluate the inclusion of 0, 10, 20, and 30 % of breadfruit tree meal as partial substitute for corn in conventional feedstuffs, for the feeding of fattening swine. An analysis of variance was performed according to one-way design with four treatments and four repetitions. In all the treatments, the maximum viability (100 %) was obtained and there were no differences for the feed intake (175 kg/pig). The treatments with 0 and 10 % of breadfruit tree meal did not differ between themselves for the final liveweight (78.25 and 77.25 kg/pig), average daily gain (ADG) (720 and 707 g/pig), conversion (3.47 and 3.54) and carcass yield (73.85 and 73.36 %). However, with 10 % of breadfruit tree meal, the feed cost/t of liveweight was reduced in 76.94 USD and per carcass ton in 92.97. The diets with 20 and 30 % of breadfruit tree meal reduced the final liveweight (74.25 and 70.33 kg/pig), the ADG (668 and 608 g/pig), and the carcass yield (72.68 and 72.39 %), besides impairing the feed conversion (3.74 y 4.11). It is recommended to use up to 30 % of breadfruit tree meal in fattening swine feedstuffs, even when it would be necessary to have more days in this category. This would permit obtaining productive results similar to those of the conventional diets and reducing the feeding cost, not changing the beef quality. Key words: breadruit tree, fattening swine.